2015
DOI: 10.1161/circulationaha.115.015607
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated Fat Intake Estimated by Circulating Biomarkers and Risk of Cardiovascular Disease and All-Cause Mortality in a Population-Based Cohort of 60-Year-Old Men and Women

Abstract: Background-High intake of polyunsaturated fatty acids (PUFAs) may reduce the risk of cardiovascular disease (CVD) and mortality. Large, prospective studies including both sexes and circulating PUFAs as dietary biomarkers are needed. We investigated sex-specific associations of the major dietary PUFAs, eicosapentaenoic acid, docohexaenoic acid, linoleic acid, and α-linolenic acid, with incident CVD and all-cause mortality in a population-based cohort. Methods and Results-PUFAs in serum cholesterol esters were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 50 publications
(76 reference statements)
5
36
0
1
Order By: Relevance
“…in heart failure 27 ), our observations can be considered supportive of a beneficial association between DPAn-3 and total mortality. Our null findings for ALA agree with some previous studies 8, 14 , but ALA levels have been associated with CVD death 26 , and ALA intake was associated with reduced total mortality in a large RCT from Spain 28 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…in heart failure 27 ), our observations can be considered supportive of a beneficial association between DPAn-3 and total mortality. Our null findings for ALA agree with some previous studies 8, 14 , but ALA levels have been associated with CVD death 26 , and ALA intake was associated with reduced total mortality in a large RCT from Spain 28 .…”
Section: Discussionsupporting
confidence: 92%
“…For example, LA – which is a major driver of the n-6:n-3 ratio – is not in the PUFA Factor score, and this may have contributed to the superior predictive power of this metric. The reason for this may be that LA is actually protective (based on the findings of 4 previous studies 79, 14 ; it was neutral in the present study), not harmful; and to include a “protective” FA in with other “harmful” FAs in the same term (total n-6) adds unnecessary noise and obscures the signal. The fact that the simpler ARA/EPA metric had similar predictive power as the n6:n3 ratio despite its non-inclusion of LA, suggests that the other FAs in the Factor score that are not present in this simple ratio (e.g., DHA, and the longer-chain products of ARA) appear to contribute to its improved predictive value.…”
Section: Discussionmentioning
confidence: 54%
“…Previous studies on the long-term effects plasma n6-fatty acids on death were done in patients not known to be HIV-infected and showed that higher linoleic acid levels, but not other n6-fatty acids, were associated with a reduced risk of all-cause mortality. 21,22 These studies are consistent with short-term or cross-sectional studies showing inverse associations between n6-fatty acids and the metabolic syndrome or its components in HIV-uninfected individuals. 23 Studies on effects of n6-fatty acids on outcomes of HIV-infection have been conducted either in vitro or have focused on short-term clinical measures such as inflammation or pregnancy outcomes in HIV-infected patients.…”
Section: Discussionsupporting
confidence: 71%
“…Although there are no epidemiologic studies investigating the direct effect of n6-fatty acids on medium- and long-term clinical outcomes in HIV/AIDS patients, studies from elderly non-HIV participants (>65 years) in the US 21 and Sweden (age>60 years) 22 show that higher plasma levels of linoleic acid, but not gamma-linolenic acid or dihomo-gamma-linolenic acid or arachidonic acid, are inversely associated with reduced risk of all-cause mortality, in part supporting the inverse association observed for linoleic acid in our study. Another study that pooled 83,349 women from the Nurses’ Health Study and 42,884 men from the Health Professionals Follow-up Study also showed that total n6-PUFA, linoleic acid and arachidonic acid estimated from food frequency questionnaires were associated with a 10-15% lower risk of all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Nyere biomarkør-studier støtter at et høyere inntak av flerumettet fett er forbundet med lavere risiko for koronar hjertesykdom [244][245][246][247] . Slike funn er imidlertid vanskelig å tolke og kan ikke «oversettes» til kvantitative råd om inntak ettersom studiene måler andeler av fettsyrer i vev.…”
Section: Biomarkører På Fettinntakunclassified